2021
DOI: 10.1002/anie.202105253
|View full text |Cite
|
Sign up to set email alerts
|

Programmable RNA N1‐Methyladenosine Demethylation by a Cas13d‐Directed Demethylase

Abstract: N1‐methyladenosine (m1A) is a prevalent and reversible RNA modification, which plays a crucial role in the regulation of RNA fate and gene expression. However, the lack of tools to precisely manipulate m1A sites in specific transcripts has hindered efforts to clarify the association between a specific m1A‐modified transcript and its phenotypic outcomes. Here we develop a CRISPR‐Cas13d‐based tool called reengineered m1A modification valid eraser (termed “REMOVER”) for targeted m1A demethylation of a specific tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Aurora A has been demonstrated as a key protein to promote cilia disassembly 24,25 . In the initiation of ciliary disassembly, Aurora A is phosphorylated and activated at the basal body, and then phosphorylates and activates HDAC6 (histone deacetylase 6), which in turn deacetylates and destabilizes axonemal tubulin to further facilitate ciliary disassembly 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aurora A has been demonstrated as a key protein to promote cilia disassembly 24,25 . In the initiation of ciliary disassembly, Aurora A is phosphorylated and activated at the basal body, and then phosphorylates and activates HDAC6 (histone deacetylase 6), which in turn deacetylates and destabilizes axonemal tubulin to further facilitate ciliary disassembly 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the demethylation activity of ALKBH3 on mRNA is inhibited by the mutation of D193A 7,24 , we generated a catalytically inactive mutant of ALKBH3 (ALKBH3-D193A) to examine whether the regulation of ALKBH3 in ciliogenesis is depend on its demethylation activity. The LC-MS/MS quantification of m 1 A mRNA modification in RPE-1 cells confirmed that the ALKBH3-D193A construct we made was indeed catalytically inactive (Supplementary Fig.…”
Section: Alkbh3 Inhibits Ciliogenesis In An M 1 A-dependent Mannermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, catalytically inactive Cas13 (dCas13) has strong and specific RNA-binding activity. This allowed the creation of fusion proteins (e.g., dRfxCas13d-ALKBH3 [ 45 ], dPspCas13b-ADAR2 [ 151 ], dRfxCas13d-ALKBH5 and dRfxCas13d-METTL3 [ 152 ]) for precise control of epitranscriptome modifications of individual target genes. Further development and research involving CRISPR/Cas13 is a promising direction for basic research on the role of individual ncRNAs, as well as a tool for targeted modification of the aberrant epitranscriptome profile of glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Writers of m1A contain tRNA Methyltransferase 6 Non-Catalytic Subunit (TRMT6)—which can be located in the nucleus or cytoplasm and which methylates adenosine in tRNA as well as in mRNA [ 39 , 40 ]—and nucleomethylin, which has only nucleolar localization and methylates 28S rRNA [ 41 , 42 ]. Erasers of m1A include ALKBH1, ALKBH3 and FTO [ 43 , 44 , 45 ]. Readers of m1A comprise YTHDF1-3 and YTHDC1 [ 46 , 47 ].…”
Section: Post-transcriptional Modificationsmentioning
confidence: 99%